Determination of Optimal Number of Vitriﬁed Human Autologous or Donor Oocytes Needed for One Live Birth - Valkova , Lyuboslava; Andreeva , Petya; Milachich , Tanya; Bandreva , Boryana; Penkova , Petya; Bochev , Ivan; Petkova, Boryana; Timeva , Tanya; Shterev , Atanas (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(4): 384–388